2009
DOI: 10.2341/08-043-l
|View full text |Cite
|
Sign up to set email alerts
|

Nanohybrid Resin Composites: Nanofiller Loaded Materials or Traditional Microhybrid Resins?

Abstract: SUMMARYNanohybrid resin composites present conventional particles to be mixed with nanomeric fillers and, therefore, it is unknown whether they may perform similarly to nanofilled or microhybrid resins. The current study investigated the properties of nanohybrid resins (TPH 3 , Grandio, Premise, Concept Advanced) in comparison with a nanofilled (Supreme XT) and a microhybrid (Z250) composite. The inorganic fillers were characterized by SEM/EDS analysis. Diametral tensile strength (DTS), surface roughness befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
100
1
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(114 citation statements)
references
References 15 publications
3
100
1
10
Order By: Relevance
“…These results is supported by other studies that found no correlation between the surface hardness and DTS values for different ranges of resin-based materials [47,69,70]. On the contrary, Medeiros et al found a strong correlation between the surface hardness and the DTS values [26].…”
Section: Discussionsupporting
confidence: 75%
“…These results is supported by other studies that found no correlation between the surface hardness and DTS values for different ranges of resin-based materials [47,69,70]. On the contrary, Medeiros et al found a strong correlation between the surface hardness and the DTS values [26].…”
Section: Discussionsupporting
confidence: 75%
“…The surface roughness has been decreased by decreasing the filler size 18) and increasing the filler content 11) . Use of a finer filler size results in less interparticle spacing, more protection of the softer resin matrix and less filler plucking 21) ; however, during polishing, it is still difficult to avoid the occurrence of irregularities at the interface between the filler particles and the resin because they have different levels of hardness 32) . According to the results of this study, the second null hypothesis, that there would be no significant differences in surface roughness among the different types of composite for each polishing system, was rejected.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from traditional hybrid and micro-hybrid composites, nano-fill and nano-hybrid composites represent the state of the art in terms of filler formulation 19) . Regarding surface roughness after polishing, nano-hybrids may not perform like nanofilled composites 17,21) , but their performance is similar to or slightly better than that of micro-hybrids 21) . To our knowledge, there is no comparison in the literature of surface roughness among the micro-hybrid, nanohybrid and supra-nanofilled composites polished with two-step polishing systems.…”
Section: Introductionmentioning
confidence: 99%
“…4 The degradation of resin composites is a complex mechanism that depends on the characteristics of the composite, such as the size, 17 volume and type of inorganic filler, 2,4,18 matrix composition, and degree of conversion. 19 The most likely explanation for degradation is the presence of nanosized particles (5-20 nm) throughout the resin matrix, 7 which results in less space between the particles, and ultimately more protection of the softer resin matrix 4,20 and less filler plucking, 20 compared with other types of resins. This leads to lower resin porosity 21 and improved abrasion resistance of the material.…”
Section: Discussionmentioning
confidence: 99%